Nebulized Furosemide for the Management of Dyspnea: Does the Evidence Support Its Use? - Newton, Phillip; Davidson, Patricia; Macdonald, P.; Ollerton, R.; Krum, H. (Elsevier, 2008)
Dyspnea is a common and distressing symptom associated with multiple chronic illness and high levels of burden for individuals, their families and health care systems. The subjective nature dyspnea and a poor understanding of pathophysiological mechanisms challenge the clinician in developing management plans. Nebulized furosemide has been identified as a novel approach to dyspnea management. This review summarizes published studies, both clinical and experimental, reporting the use of nebulized furosemide. The search criteria yielded 42 articles published in the period 1988 to 2004. Although nebulized furosemide appeared to have a positive influence on dyspnea and physiological measurements, caution must be taken with the results primarily coming from small-scale clinical trials or observation trials. Despite the limitations of the studies reported, given the range of conditions reporting effectiveness of nebulized furosemide, further investigation of this potential novel treatment of dyspnea is warranted.